Correlation between Hemoglobin Concentration and Cardiorespiratory Fitness in Adolescent Sportsmen - Billy Leoprayogo; Venna Venna; Ignatio Rika Haryono; Francisca Tjhay (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Sport is a physical activity that increases human body oxygen demand. Hemoglobin has a major role to fulfill the oxygen demand. The body capacity to fulfill the increasing oxygen demand could be seen as cardiorespiratory fitness. Sportsmen have a high cardiorespiratory fitness due to the intensity and frequency of training. This study aimed to explore how hemoglobin concentration affects the cardiorespiratory fitness of adolescence sportsmen. Method: This study used a cross-sectional approach. The sampling started in October – November 2019. Sample of this study were 15-19 years old male badminton and basketball sportsmen at Jakarta and Bogor (n=72). Hemoglobin concentration measured with a digital hemoglobinometer which used an azide-methemoglobin method. VO2max estimated with a beep test. FITNESSGRAM® Performance Standard was used for the classification of cardiorespiratory fitness. All measurement’s ethical issues had been approved. The result of hemoglobin concentration and cardiorespiratory fitness was processed by SPSS program with Spearman and Kruskal-Wallis analysis method. Results: There was a correlation between hemoglobin concentration and cardiorespiratory fitness (p = 0.001, p < 0.05). Spearman analysis showed there was a weak correlation (r = 0.38) between hemoglobin concentration and cardiorespiratory fitness. Kruskal-Wallis analysis showed there was a meaningful mean difference in hemoglobin concentration on cardiorespiratory fitness groups (p = 0.005, p < 0.05). Conclusion: The mean of the hemoglobin concentration on the Healthy Fitness Zone (HFZ) cardiorespiratory group was higher than on the Need Improvement (NI) group and the Need Improvement within Health Risk (NI-HR) group.